2021
DOI: 10.5897/ajmr2020.9462
|View full text |Cite
|
Sign up to set email alerts
|

A study of bacterial pathogens associated with diarrhoea in children under 2 years in Ile-Ife, Nigeria

Abstract: Diarrhoea, a major contributor to high mortality in children may be caused by an array of bacterial, viral or parasitic pathogens acting individually or synergistically. This study identified the bacterial pathogens associated with diarrhoea in children aged 0-24 months, established the frequency of diarrhoea caused by each pathogen encountered in diarrhoea and determined the antibiotic resistance pattern of the children's faecal isolates obtained to some commonly used antibiotics in the study environment. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…recovery (Joseph et al, 2017;Akinwumi et al, 2021), adding to evidence supporting earlier speculation that this pathogen may be less important in this setting and therefore the importance of understanding pathogen epidemiologies in a range of settings (Lindsay et al, 2015;Okeke et al, 2016).…”
Section: Enteric Pathogen Detection In Diarrhoea Stools and Co-infect...mentioning
confidence: 81%
See 1 more Smart Citation
“…recovery (Joseph et al, 2017;Akinwumi et al, 2021), adding to evidence supporting earlier speculation that this pathogen may be less important in this setting and therefore the importance of understanding pathogen epidemiologies in a range of settings (Lindsay et al, 2015;Okeke et al, 2016).…”
Section: Enteric Pathogen Detection In Diarrhoea Stools and Co-infect...mentioning
confidence: 81%
“…(2016 ) reported EIEC association with diarrhoea in patients from Spain. Meanwhile, recent studies in Nigeria have not recovered Shigella or reported relatively low recovery ( Joseph et al., 2017 ; Akinwumi et al., 2021 ), adding to evidence supporting earlier speculation that this pathogen may be less important in this setting and therefore the importance of understanding pathogen epidemiologies in a range of settings ( Lindsay et al., 2015 ; Okeke et al., 2016 ).…”
Section: Resultsmentioning
confidence: 97%